2009
DOI: 10.1371/journal.pone.0004384
|View full text |Cite|
|
Sign up to set email alerts
|

MF59®-Adjuvanted H5N1 Vaccine Induces Immunologic Memory and Heterotypic Antibody Responses in Non-Elderly and Elderly Adults

Abstract: BackgroundPathogenic avian influenza virus (H5N1) has the potential to cause a major global pandemic in humans. Safe and effective vaccines that induce immunologic memory and broad heterotypic response are needed.Methods and FindingsHealthy adults aged 18–60 and >60 years (n = 313 and n = 173, respectively) were randomized (1∶1) to receive two primary and one booster injection of 7.5 μg or 15 μg doses of a subunit MF59-adjuvanted H5N1 (A/Vietnam/1194/2004) (clade 1) vaccine. Safety was monitored until 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
131
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 26 publications
(38 reference statements)
18
131
1
2
Order By: Relevance
“…[12][13][14] Previous clinical studies have demonstrated that an MF59-adjuvanted seasonal trivalent influenza vaccine induced higher and broader antibody responses compared with nonadjuvanted vaccines, especially in subjects with low prevaccination antibody titers and with a confirmed safety profile in vulnerable populations, including the elderly, those with underlying chronic conditions and children. 9,[12][13][14][15][16][17][18][19][20][21][22][23] The EMA had initially recommended a 2-dose administration schedule at least 21 days apart for the centrally authorized pandemic vaccines based on existing data from H5N1 vaccines. 24,25 Subsequently published immunogenicity and safety data from H1N1v clinical trials demonstrated that the administration of a single dose of vaccine would be sufficient to elicit robust immune responses that comply with international licensing criteria.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] Previous clinical studies have demonstrated that an MF59-adjuvanted seasonal trivalent influenza vaccine induced higher and broader antibody responses compared with nonadjuvanted vaccines, especially in subjects with low prevaccination antibody titers and with a confirmed safety profile in vulnerable populations, including the elderly, those with underlying chronic conditions and children. 9,[12][13][14][15][16][17][18][19][20][21][22][23] The EMA had initially recommended a 2-dose administration schedule at least 21 days apart for the centrally authorized pandemic vaccines based on existing data from H5N1 vaccines. 24,25 Subsequently published immunogenicity and safety data from H1N1v clinical trials demonstrated that the administration of a single dose of vaccine would be sufficient to elicit robust immune responses that comply with international licensing criteria.…”
Section: Resultsmentioning
confidence: 99%
“…MF59 has been licensed in Europe as well for pandemic influenza vaccines and has been widely used for the 2009 H1N1 pandemic flu campaign (16). Clinical trials conducted using avian H5 pandemic flu antigens have demonstrated that MF59 allowed for antigen dose sparing and increased seroconversion and cross-protection in vaccinees (17). A recent study has shown that in infants MF59 increases the efficacy of the Trivalent Inactivated influenza Vaccine from 43% to 89%.…”
mentioning
confidence: 99%
“…against H5N1, two-dose vaccination schedules were needed, irrespective of adjuvant content. [8][9][10] The hemagglutinin of the influenza virus causing the 2009 pandemic was derived from the 1918 influenza A strain that entered swine around that time.…”
Section: Resultsmentioning
confidence: 99%
“…Squalene-based emulsion adjuvants had been used to enhance the immunogenicity of the poorly immunogenic H5N1 avian influenza virus vaccines in various age groups, [8][9][10] as well as seasonal influenza vaccines for the elderly and young children who…”
Section: Introductionmentioning
confidence: 99%